Releasing financial pressure through released time religious education: the fiscal impact of one released time programme on a state’s funding for public education - Calvert, Isaac (British Journal of religious education, 2025)
We sought to quantify the fiscal impact of the Church of Jesus Christ of Latter-day Saints’ released time programme in the state of Utah, in the United States of America, on funding for American public education. The guiding research question for this study was: How much money does the Church of Jesus Christ of Latter-day Saints’ seminary programme save public education in the state of Utah? We collected data from one school district in Utah and then extrapolated those findings, on a per pupil basis, to the entire state. Findings are reported in three approximates of the actual fiscal impact of the Church’s seminary programme in Utah: high, medium, and low. Our conclusion is that the actual fiscal impact of seminary on funding for public education lies within this reported range. We report that the Church’s seminary programme saves the state of Utah between USD45,000,000 and USD64,000,000 annually. While these figures only constitute 0.6% to 0.8% of the total funding for public education, this released time programme provides district officials with financial and scheduling flexibility. In addition, there are indirect fiscal benefits associated with seminary as well as direct and indirect costs.